Exact Determinants of Some Special Circulant Matrices Involving Four Kinds of Famous Numbers - Xiaoyu Jiang; Kicheon Hong (Abstract and Applied Analysis)
Circulant matrix family is used for modeling many problems arising in solving various differential equations. The RSFPLR circulant matrices and RSLPFL circulant matrices are two special circulant matrices. The techniques used herein are based on the inverse factorization of polynomial. The exact determinants of these matrices involving Perrin, Padovan, Tribonacci, and the generalized Lucas number are given, respectively.